Macrophage Migration Inhibitory Factor Release by Macrophages after Ingestion of Plasmodium chabaudi-Infected Erythrocytes: Possible Role in the Pathogenesis of Malarial Anemia - Martiney, James A. (American Society for Microbiology, 2000)
Human falciparum malaria, caused by Plasmodium falciparum infection, results in 1 to 2 million deaths per year, mostly children under the age of 5 years. The two main causes of death are severe anemia and cerebral malaria. Malarial anemia is characterized by parasite red blood cell (RBC) destruction and suppression of erythropoiesis (the mechanism of which is unknown) in the presence of a robust host erythropoietin response. The production of a host-derived erythropoiesis inhibitor in response to parasite products has been implicated in the pathogenesis of malarial anemia. The identity of this putative host factor is unknown, but antibody neutralization studies have ruled out interleukin-1β, tumor necrosis factor alpha, and gamma interferon while injection of interleukin-12 protects susceptible mice against lethal P. chabaudi infection. In this study, we report that ingestion of P. chabaudi-infected erythrocytes or malarial pigment (hemozoin) induces the release of macrophage migration inhibitory factor (MIF) from macrophages. MIF, a proinflammatory mediator and counter-regulator of glucocorticoid action, inhibits erythroid (BFU-E), multipotential (CFU-GEMM), and granulocyte-macrophage (CFU-GM) progenitor-derived colony formation. MIF was detected in the sera of P. chabaudi-infected BALB/c mice, and circulating levels correlated with disease severity. Liver MIF immunoreactivity increased concomitant with extensive pigment and parasitized RBC deposition. Finally, MIF was elevated three- to fourfold in the spleen and bone marrow of P. chabaudi-infected mice with active disease, as compared to early disease, or of uninfected controls. In summary, the present results suggest that MIF may be a host-derived factor involved in the pathophysiology of malaria anemia.